2023
DOI: 10.3390/nu15061484
|View full text |Cite
|
Sign up to set email alerts
|

Both Saccharomyces boulardii and Its Postbiotics Alleviate Dextran Sulfate Sodium-Induced Colitis in Mice, Association with Modulating Inflammation and Intestinal Microbiota

Abstract: Objective: To investigate the effect of Saccharomyces boulardii and its freeze-dried and spray-dried postbiotics on the intervention and potential mechanism of dextran sulfate sodium (DSS)-induced ulcerative colitis in mice. [Methods] After the acclimation period of C67BL/6J mice, a colitis model was constructed by applying 2% DSS for 7 d, followed by 7 d of intervention. Subsequently, the disease activity index (DAI), organ index, colon length, colon HE staining of pathological sections, ELISA for blood infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…Studies have reported that Bacteroidota was negatively correlated with UC activity indicators, and the aggravation of UC will lead to the disappearance of these species [ 45 ]. After CON treatment, the abundance of Bacteroidota increased and Firmicutes decreased; this finding was similar to that reported by Xu et al [ 46 ]. F/B value effectively reflect the imbalance of the intestinal flora [ 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…Studies have reported that Bacteroidota was negatively correlated with UC activity indicators, and the aggravation of UC will lead to the disappearance of these species [ 45 ]. After CON treatment, the abundance of Bacteroidota increased and Firmicutes decreased; this finding was similar to that reported by Xu et al [ 46 ]. F/B value effectively reflect the imbalance of the intestinal flora [ 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…Accumulating research has indicated that postbiotics have similar or even better effects than their active bacteria [7]. Compared with live strains, postbiotics of Saccharomyces boulardii showed better efficacy in alleviating dextran sulfate sodium-induced colitis by modulating inflammation and intestinal microbiota in mice [8]. The killed lactic acid bacteria exhibited better immunomodulatory activities than live probiotic in mice spleen cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…On day 28, the mice were fasted for 7 h and euthanized by cervical dislocation after collecting blood from the orbit [27]. Blood samples were immediately placed in a centrifuge tube, placed in a water bath at 37 • C for 1-2 h, and then stored at 4 • C for 3-4 h. The blood clot was retracted and centrifuged at 3000× g for 15 min, and the serum was collected as the supernatant [28].…”
Section: Biochemical Assays Of Serummentioning
confidence: 99%